Implementation of Character Education in the Establishment of Students National Value During the Covid-19 Pandemic - Fajrussalam, Hisny; Adya Winata, Koko; Ruswandi, Uus; Nursobah, Asep (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Abstract: The pandemic period has resulted in changes in habits in all sectors of life, including in education. This study aims to describe the implementation of character education in the formation of national values during the pandemic. The method used in this research is descriptive qualitative. The research was conducted at SDN 002 Cicadas Bandung. The data was obtained by conducting in-depth interviews with the specified informants: principals, homeroom teachers, teachers, and students. The consideration of being specified is source triangulation and it is part of the data validity stage. Research data is analyzed using several data analysis steps, namely data reduction, data classification and data verification. The study results indicated that the implementation of character education in the formation of national values during the pandemic can be done through; a) national character habituation activities, b) integration of character materials related to national values and c) forming online national discussion groups.